2019
DOI: 10.1101/799056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hox gene expression during the development of the phoronidPhoronopsis harmeri

Abstract: Background: Phoronida is a small group of marine worm-like suspension feeders, which together with brachiopods and bryozoans form the clade Lophophorata. Although their development is well studied on the morphological level, data regarding gene expression during this process are scarce and restricted to the analysis of relatively few transcription factors. Here we present a description of the expression patterns of Hox genes during the embryonic and larval development of the phoronid Phoronopsis harmeri. Resul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 118 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, molecular studies in rhynchonelliform and craniiform brachiopods demonstrated that the early embryonic patterning is defining the mode of gastrulation as protostomic or deuterostomic [4]. However, with the exception of Hox genes [5], molecular studies on embryonic development of phoronids are still lacking and are therefore important to understand the precise timing of germ layer segregation and cell specification. Furthermore, due to their informative phylogenetic position (as sister group, together with Ectoprocta, to Brachiopoda), phoronids can shed light on whether a similar developmental mode is shaped by conserved molecular mechanisms in closely related taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, molecular studies in rhynchonelliform and craniiform brachiopods demonstrated that the early embryonic patterning is defining the mode of gastrulation as protostomic or deuterostomic [4]. However, with the exception of Hox genes [5], molecular studies on embryonic development of phoronids are still lacking and are therefore important to understand the precise timing of germ layer segregation and cell specification. Furthermore, due to their informative phylogenetic position (as sister group, together with Ectoprocta, to Brachiopoda), phoronids can shed light on whether a similar developmental mode is shaped by conserved molecular mechanisms in closely related taxa.…”
Section: Introductionmentioning
confidence: 99%